Bioatividade de peptídeos do soro de leite obtidos por hidrólise e ultrafiltração em condições gastrointestinal simuladas - Costa, Luan Felipe Santana (2021)
Bovine whey has multiple health-promoting attributes and is a source of biopeptides with high biological value. The objective of the work was to hydrolyze whey proteins to produce peptides purified by ultrafiltration, evaluating the gastrointestinal effect on the bioactivity of these peptides. The hydrolysis of concentrated whey proteins was performed by combining two proteolytic enzymes (Alcalase and Neutrase), using a 10 kDa ultrafiltration membrane to purify the peptides produced. Afterwards, the peptides were taken to gastrointestinal simulation in vitro, evaluating their effect on different biological activities of the peptides (antioxidant and anti-inflammatory activity). The results indicated that the combination of Alcalase and Neutrase enzymes significantly increases the degree of hydrolysis, in conjunction with Ultrafibration operation, allows obtaining low molecular weight peptides with improved biological activity after digestion. The values at the end of the intestine stage by the ABTS radical inhibitor method with whey protein concentrate (CPS) were (10.79 ± 0.85 μmol TE / g protein), hydrolyzed permeate of Alkalase + Neutrase (A + N) (18.02 μmol TE / g protein); FRAP with CPS (1.4 μmol TE / g protein), A + N (5.16 μmol TE / g protein); Anti-HOCl method with CPS (34.91 ± 0.085 μmol of AC / g of protein) A + N (38.72μmol of AC / mg of protein), Anti-α-Amylase with CPS IC 50 (0.086 ± 0.007 g of protein / ml), A + N IC 50 (0.063 ± 0.0039 g protein / ml). The results of the combination of enzymes, combined with ultrafiltration, decreased the molecular weight and improved the bioavailability, contributing to the development of peptides with greater functional capacity in relation to the integral protein after digestion. The molecular profile showed a decrease in proteins of molecular weight from 100 to 250 kDa after Ultrafiltration, proving that UF is a suitable method for the purification of low molecular weight peptides, with exclusive peptides <10kDa being found. Thus, bioactivity can be improved with digestion combined with hydrolysis and ultrafiltration, especially rapid change occurs when pancreatic enzymes are added. Bioactivities such as the anti-inflammatory, anti-diabetic and antioxidant action are related to the peptides released by the action of pancreatic enzymes, observing a rapid increase after the addition of these enzymes. Although there are no significant differences in the anti-inflammatory action of the peptides after digestion, an improvement was observed in relation to the integral protein. Digestion alters the peptide profile, the results suggest a strong application potential of the peptides as an ingredient of food enrichment, functional food and supplementation with the purpose of Antioxidant, Anti-inflammatory and Antidiabetic action.